2017
DOI: 10.1093/icvts/ivx286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of initial aortic diameter and false-lumen area ratio on Type B aortic dissection prognosis†

Abstract: UMIN 000025388, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000029229.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
6
15
0
1
Order By: Relevance
“…Many risk factors for late aortic events have been identified [7][8][9][10][11][12][13][14][15] ; however, a robust risk model predicting late aortic events after UTBAD has not been established. This study was performed to build a risk prediction score model for late aortic events in patients with UTBAD and validate it using large-size clinical data with a high follow-up rate.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Many risk factors for late aortic events have been identified [7][8][9][10][11][12][13][14][15] ; however, a robust risk model predicting late aortic events after UTBAD has not been established. This study was performed to build a risk prediction score model for late aortic events in patients with UTBAD and validate it using large-size clinical data with a high follow-up rate.…”
Section: Perspectivementioning
confidence: 99%
“…16 We described our acute aortic dissection protocol in a past study. 7 All cases of UTBAD were managed medically regardless of the false lumen status or the aortic diameter. Medical management included admission to the intensive care unit, continuous blood pressure monitoring, central venous access for intravenous antihypertensive medication, and urine output monitoring.…”
Section: Derivation Cohort Studymentioning
confidence: 99%
“…Acute type B was defined as that involving the descending aorta (without any tear in or involvement of the ascending aorta) appearing within 14 days of the onset of symptoms. [ 7 8 9 ] Patients were divided into two groups according to sex.…”
Section: Ethodsmentioning
confidence: 99%
“…12,13 However, a recent study of acute type B dissection, perhaps a surrogate for the distal segment following hemiarch repair, reported no effect of false lumen patency on late survival. 15 Many studies have shown that a frozen elephant trunk does promote false lumen thrombosis at the level of the stent, but not at the diaphragmatic and visceral segment levels. For example, Zhang and colleagues reported 100% proximal thrombosis at 6À12 months but only 45.1% distally.…”
Section: False Lumen Patency Post Hemiarchmentioning
confidence: 99%
“…A frequent cutoff differentiating excellent from inferior outcomes is 40 mm. 9,15,30,32,33 False lumen patency is another parameter often correlated with outcomes, and studies have variously focused on false lumen size, 11,30,35 shape, degree of thrombosis, 36 and capacity of outflow branches. 37 An important observation regarding false lumen measurements in the acute phase is that the dissection membrane is dynamic and moves throughout the cardiac cycle, making false lumen size measurement by one fixed CT image misleading.…”
Section: Selective Use Of Extended Procedures For Ataadmentioning
confidence: 99%